Jejunal Dieulafoy’s Lesion as a Rare Cause of Massive Gastrointestinal Bleeding; a Case Report and Literature Review - Kalantari, Mohammad Ebrahim; Sardarzadeh, Newsha; Mirsadeghi , Ali; Bagherzadeh, Ali Akbar; Zandbaf, Tooraj (Archives of Academic Emergency Medicine, 2022)
Jejunal Dieulafoy's lesion is difficult to diagnose due to its rarity, intermittent hemorrhage, and lesion site, which is largely inaccessible to conventional endoscopes. A 39-year-old man, who had no underlying disease, presented to the emergency department (ED) with weakness, dizziness, and dry cough with a history of several rectal bleeding episodes in the last few years. Endoscopy was normal, and the colon was full of clots on colonoscopy, and no gross pathology was found. On computed tomography (CT) angiography, a hyperdensity was seen in the middle of the jejunum, possibly suggesting contrast extravasation. Due to decreased hemoglobin of the patient, and hemodynamic instability, the patient became a candidate for surgery. A palpable lesion in the Jejunum was touched that opened longitudinally, which revealed active arterial bleeding from the nipple-like lesion. This segment was resected, and an anastomosis was performed. Histopathological examination of the small intestine confirmed a Dieulafoy’s lesion. It seems that, when upper endoscopy and colonoscopy fail to identify the cause of gastrointestinal bleeding, a Dieulafoy’s lesion should be included in the differential diagnoses.